ASSESSMENT OF SOIL QUALITY AND HEALTH USING SOME PHYSICAL AND BIOLOGICAL PROPERTIES FOR FADAK FARM PROJECT - Taha T. Alwazzan; Alaa Salih Ati (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Fadak farm project was selected to conduct this study and to evaluate the state of quality and health indices in term of soil physical and biological properties, where this farm is located in Holly Najaf Governorate. Some physical properties (soil texture, mean weight diameter, bulk density, porosity, infiltration rate, saturated hydraulic conductivity and available water) were selected to assess the quality then health indices, and the biological characteristics (vegetation coverage, soil respiration, bacterial and fungal counts) were also selected to assess the quality and health indices in term of these properties. Results showed that classes of moderate and poor soil health were dominated in lands of this farm for each physical and biological properties. It was noted that the class good of soil health was collaterally appeared in small areas according to biological characteristics.